The Self-Esteem, Moral Courage, and Whistleblowing: Case of Corporate Accounting Staff in Indonesia - Mukhlasin Mukhlasin (Jurnal Dinamika Akuntansi, 2022)
Research purposes: This research aims to examine the relationship between self-esteem, moral courage, and internal whistleblowing intentions. The primary research framework uses prosocial theory to build logic to develop hypotheses.Methods: This research was designed as a survey method on the corporate accounting staff in Indonesia. Data collection by convenience sampling method with google Forms online. A sample of 184 respondents was tested by the maximum likelihood Structural Equation Model (SEM) with an asymptotic covariance matrix. This method was used because the multivariate data were non-normally distributed.Findings: The proven that moral courage encourages internal whistleblowing. Meanwhile, self-esteem doesn’t motivate employee intention to internal whistleblowing. Self-esteem is established as a determinant of moral courage. This evidence shows that moral courage is meditating.Novelty: Theoretically, this study contributes that self-esteem is an intrapersonal variable that can encourage employee intention of the internal whistleblower. In contrast to previous studies that examined professional accountants, internal audits, external audits, and employees, this study was conducted on corporate accounting staff.